2002
DOI: 10.1191/0961203302lu132oa
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in levels of antiphospholipid antibodies and increased coagulation activation markers in normal andheparin-treated antiphospholipid syndrome pregnancies

Abstract: Antiphospholipid antibodies (aPL) are associated with an increased risk of thrombosis and recurrent miscarriage. We assessed levels of coagulation activation markers and aPL during normal pregnancy and in women with the antiphospholipid syndrome (aPS). Fluctuations in aPL levels were observed in all patients with aPS. No particular pattern of antibody positivity, or fluctuation in aPL level, was associated with poor pregnancy outcome. A significant increase was observed in levels of factor Xlla (FXIIa; P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 41 publications
0
22
0
2
Order By: Relevance
“…Factor XIII, fibrinstabilizing factor, increases in the early stages of pregnancy, returning to non-pregnant values in the third trimester [12]. Levels of factor XII, X and IX increase progressively during pregnancy [13][14][15][16]. In contrast, levels of factor XI decrease during pregnancy [13], and it has previously been suggested that this may be a consequence of increased factor XI consumption [17].…”
Section: Coagulation Factor Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…Factor XIII, fibrinstabilizing factor, increases in the early stages of pregnancy, returning to non-pregnant values in the third trimester [12]. Levels of factor XII, X and IX increase progressively during pregnancy [13][14][15][16]. In contrast, levels of factor XI decrease during pregnancy [13], and it has previously been suggested that this may be a consequence of increased factor XI consumption [17].…”
Section: Coagulation Factor Changesmentioning
confidence: 99%
“…Levels of vWF (von Willebrand factor), which serves as a carrier for factor VIII and plays a role in platelet adhesion, also increase progressively in pregnancy [18,20]. Factor VII also increases gradually during normal pregnancy [14][15][16][17]. Increases in factor V concentration in early pregnancy are followed by a decrease and stabilization [15], whereas factor V coagulation activity (Vc) shows a gradual rise throughout gestation [18].…”
Section: Coagulation Factor Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…По дан-ным некоторых исследователей, Mac-1 моноци-тов периферической крови может связываться с фактором X каскада свертываемости крови [19], в результате моноциты могут индуцировать фор-мирование протромбиназного комплекса. Таким образом, повышение количества CD11b + моно-цитов беременности может быть одной из при-чин повышения прокоагулянтной активности, предрасполагающей к развитию тромбофиличе-ских осложнений [6].…”
Section: адгезионные молекулы при беременности 2010 т 12 № 4-5unclassified
“…7,[9][10][11][12][13][15][16][17] In the prospective studies, the effect of ACA on live birth rate has been reported very differently, The different results in the prospective studies could partly be attributed to poorly standardized ACA tests reflected in a significant interlaboratory variation in the detection of ACA significant fluctuations of the antibody levels over time in the same patient and very different cut off levels. [17][18][19][20][21][22][23][24] For an obstetrician who is treating patients with recurrent pregnancy loss, previous studies do not adequately answer the question: what are the prognostic value of an elevated ACA titre and the development of late pregnancy complications such as preeclampsia, low birth weight and preterm labour? Therefore, present study objective was to compare the prevalence of ACA in patients with recurrent pregnancy loss and normal healthy pregnant women and its association of complication and obstetric outcomes.…”
Section: Introductionmentioning
confidence: 99%